The Russian Registry of Chronic Hypoparathyroidism - Kovaleva, Elena V.; Eremkina, Anna K.; Elfimova, Alina R.; Krupinova, Julia A.; Bibik, Ekaterina E.; Maganeva, Irina S.; Gorbacheva, Anna M.; Dobreva, Ekaterina A.; Melnichenko, Galina A.; Mokrysheva, Natalia G. (Frontiers in Endocrinology, 2022)
Introduction: Chronic hypoparathyroidism is a relatively rare disease associated with multicomponent medical therapy and various complications. The analysis of large databases of patients with chronic hypoparathyroidism is a necessary tool to enhance quality of medical care, as well as to determine the optimal clinical and therapeutic approaches, and prognostic markers of the disease. The aim of this study is to estimate the clinical and biochemical profile, long-term complications, medical therapy and disease control of the patients with chronic postsurgical and non-surgical hypoparathyroidism. Materials and methods: the cross-sectional, observational, continuous study was based on the Russian Registry of patients with hypoparathyroidism. 544 patients from 63 regions of the Russian Federation were included in this study. Results: The majority of cases had postsurgical etiology (88.4%). Postsurgical hypoparathyroidism prevailed in females (р<0.001). About a half of patients had blood calcium and phosphorus targets, 56 and 52% respectively. Nephrolithiasis was confirmed in 32.5%, nephrocalcinosis - in 12.3% of cases. The risk of nephrocalcinosis/nephrolithiasis increased by 1.85 times with disease duration more than 4.5 years. The cataract was found in 9.4%. The cut-off point for the development of cataracts was 9.5 years, with a 6.96-fold increased risk. The longer duration of hypoparathyroidism of any etiology was associated with more frequent cataract (p=0.0018).We found brain calcification in 4%, arrhythmias in 7.2% and neuropsychiatric symptoms in 5.15% of cases. Generally, the BMD in the studied group corresponded to age values, and there was no evidence for the phenomenon of high bone density. TBS was consistent with normal bone microarchitectonics. In our study, the majority of patients (83.5%) was treated with standard therapy of calcium and vitamin D supplements. 5 patients with severe disease course were treated with rhPTH (1–34). Conclusions: Analysis of the presented database indicates insufficient diagnosis of the complications associated with chronic hypoparathyroidism. Overall, hypoparathyroidism is associated with higher risks of renal stone formation, decreased GFR, cataract especially in patients with longer duration of disease.